IMPACT OF COVID-19 ON RADIATION ONCOLOGY IN PAKISTAN - MASOOD , A; REHMAN , RMF; QASIM , U; ARIF, S; WAKEFIELD , DV; SCHWARTZ , DL (Biological and Clinical Sciences Research Journal, 2023)
The survey study was conducted in the Radiology Departments of different centers in Pakistan from June 2020 to October 2020 to assess the impact of COVID-19 on radiation therapy in Pakistan. Data about courses in external beam radiography and attendees were extracted from the hospital record. The percentage change in radiotherapy activity for each month between June to October 2020 was calculated and individually compared from June 2019 to October 2019. Results showed that lockdown was significantly associated with a reduction in radiotherapy courses (P<.0001). The mean weekly number of radiotherapy courses decreased by 108 (-19.9%) in June 2020 from 543±170 in June 2019. The largest reduction in radiotherapy courses after the lockdown was reported in non-melanoma skin cancer and prostate cancer. Data analysis showed that radiation therapy services fell significantly at the onset of COVID-19. Cancers whose treatment can be safely delayed were most affected. On the other hand, cancers in which radiotherapy offered an alternative to surgery had seen a rise in treatment courses.